Model Strategi Komunikasi Untuk Pelestarian Bekantan dan Habitatnya - Hairunnisa Hairunnisa; Muhammad Noor; Hariati Hariati; Annisa Wahyuni; Chatur Ganesa (Jurnal Penelitian Pers dan Komunikasi Pembangunan, 2018)
This study identified a strategy for communication campaigns carried out by the government to preserve bekantan and its habitat. Data was collected by purposive sampling method by determining key informants, primary data obtained from direct interviews with respondents based on interview guidelines, while secondary book data, documents, archives, notes, and images related to the research objectives. The results of the study indicate that in conducting campaigns to maintain coaching more effectively use communication as a strategy to convey information to a wide audience. Media used from mass media and non-mass media. The government is of the opinion that direct or face-to-face communication is considered more effective to deliver information about preserving proboscis monkey. In addition, the Government also published various pamphlets, leaflets, and books containing important information about conservation. However, the use of social media and the internet has not been used for communication campaigns about the conservation of proboscis monkeys and their habitat. There are several inhibiting factors in maintenance in wild animals in Kuala Samboja. This is caused by habitat fragmentation and land management patterns due to forest conversion and illegal activities. In addition, because of the problems of conflict, spatial planning and law enforcement and crime rates, this is also a crucial problem. Keywords: Strategy, Campaign, Bekantan, Preservation, Communication ABSTRAK Studi ini mengidentifikasi strategi kampanye komunikasi yang dilakukan oleh pemerintah untuk pelestarian bekantan dan habitatnya. Data dikumpulkan dengan metode purposive sampling, data primer diperoleh dari wawancara langsung dengan responden berdasarkan pedoman wawancara. Hasil penelitian menunjukkan bahwa dalam melakukan kampanye untuk mempertahankan pembela secara lebih efektif menggunakan komunikasi sebagai strategi untuk menyampaikan informasi kepada khalayak luas. Media yang digunakan mulai dari media massa dan media nirmassa. Pemerintah berpendapat, komunikasi langsung atau tatap muka dianggap lebih efektif untuk menyampaikan sosialisasi tentang melestarikan bekantan. Selain itu, Pemerintah juga menerbitkan berbagai pamflet, selebaran, dan buku yang berisi informasi penting tentang pelestarian. Namun, penggunaan media sosial dan internet belum digunakan untuk kampanye komunikasi mengenai pelestarian monyet bekantan dan habitatnya. Ada beberapa faktor penghambat dalam upaya pelestarian satwa liar di Kuala Samboja. Hal ini disebabkan oleh fragmentasi habitat dan pola pengelolaan lahan karena konversi hutan dan kegiatan ilegal. Selain itu, karena masalah konflik lahan, tata ruang dan penegakan hukum serta tingkat kesadaran berbagai pihak menjadikan hal ini menjadi masalah krusial. Kata kunci: Strategi, Kampanye, Bekantan, Pelestarian, Komunikasi